Mid‐term integrated generation and maintenance scheduling for wind‐hydro‐thermal systems. (12th January 2018) - Ge, Xiaolin; Xia, Shu; Su, Xiangjing
Summary: A mid‐term integrated generation and maintenance scheduling model is proposed for wind‐hydro‐thermal systems in this paper. Various constraints of wind farms, thermal plants, and cascaded hydropower reservoirs are included to develop the complementarity of different energy sources. Stochastic behaviors for wind power, natural inflow, electric power, and energy demand are modeled using chance‐constrained programming and then converted into equivalent deterministic formulations to reduce the calculation complexity. Besides, to achieve the integrated optimization for generation and maintenance scheduling, detailed maintenance constraints as well as the coupling constraints of 2 tasks are considered in the scheduling model. In addition, 2 types of time indexes are used to coordinate the different time interval requirements for them. Finally, the proposed mixed integer linear programming model is solved by commercial software CPLEX. Case studies by 2 actual systems show that the integrated generation and maintenance schedules of wind‐hydro‐thermal system outperform the other conventional schemes in terms of feasibility and economy.